Urban American Indian Adult Participation and Outcomes in Culturally Adapted and Mainstream Alcoholics Anonymous Meetings. Issue 1 (2nd January 2020) - Tonigan, J. Scott; Venner, Kamilla; Hirchak, Katherine A.
ABSTRACT: Very little is known about American Indian (AI) adults' participation in Alcoholics Anonymous (AA) despite their elevated rates of negative sequelae due to heavy alcohol consumption and alcohol use disorders. This study sought to fill that gap and examined the engagement in AA by urban Southwest AI (S-AI) adult problem drinkers and whether enculturation and acculturation accounted for type of AA attended (mainstream vs. culturally adapted AA; CA-AA). Additionally, we compared 3- and 6-month drinking outcomes of urban S-AI adults by type of meeting attended. Sixty-one urban S-AI adults consented and were assessed at baseline, 3, and 6 months. We examined the association between frequency of AA attendance and differences between types of meetings attended regressed on the outcomes of proportion abstinent days and drinks per drinking day. Results indicate that AA attendance is the model approach and assists urban S-AI adults in reducing their drinking. Despite higher engagement among those attending AA and CA-AA, this did not translate into differential AA-related benefit which speaks to the need for additional research to assist AI adults in effectively reducing their alcohol use.